Controlled extraction and characterization of ulvan from Ulva papenfussii with potential applications in sustainable energy - Troncoso Heros, Omar Paul (2025)
The industrial applications of unused natural resources are a key issue in sustainability research. Here we describe the extraction of the biopolymer ulvan, a sulfated polysaccharide, from the green alga Ulva papenfussii. Two different extraction techniques, hot water extraction and alkaline extraction, were used. Ulvan extracted using the hot water extraction method, featured an extraction yield of 29% and a sulfate content of 50% while alkaline extraction produced a yield of 21% and a sulfate content of 28%. The ulvan obtained via hot water extraction also showed a more homogeneous molecular weight distribution than the ulvan obtained with the alkaline extraction method. Flat rectangular films were prepared for characterization using a casting technique. The films prepared using hot water-extracted ulvan displayed lower glass transition and thermal degradation temperatures compared to the other samples. These biopolymeric films can be used in the development of novel materials with potential applications in the food, biomedical, and energy storage industries.